REPRESENTASI DAN PENGARUH KARAKTER PUT ON DALAM PEMBENTUKAN IDENTITAS PERANAKAN TIONGHOA YANG MEMILIKI NILAI KEINDONESIAAN - Park, Johanes (Narada : Jurnal Desain dan Seni, 2025)
"Put On" is the name of both a character and the title of a comic that was once popular in Indonesia. Put On was published around 1931 by Kho Wan Gie in the newspaper. The Put On comic showcases many aspects of the Chinese-Indonesian (Peranakan) culture residing in Jakarta. The Chinese--Indonesian cultures depicted in the comic includes language, daily habits, family structure, and the food consumed. In the Put On comic, the character Put On is shown to be mischievous, naive, and childish despite being portrayed as a large middle-aged man. This research was conducted using qualitative methods in the form of multimodal analysis and narrative inquiry. The observation through multimodal analysis was done to see the graphic narrative elements in the comic, while narrative inquiry was carried out to elaborate on the experience of reading Put On. The aspects observed in the reading experience included character design (drawing style, physical appearance, and clothing style), language (body language and speech), and visualization of social situations. The results of the study reveal that while the design and traits of Put On as the main character do not clearly exhibit a Chinese-Indonesian identity, it is the interaction with other characters who use distinctive language and the social environment they inhabit that makes the Put On comic able to represent Chinese-Indonesian culture.